The answer is blowing in the wind [hurricane prediction]. - Das, S.R.
A team of British scientists has developed a hurricane predicting technique with a forecast accuracy of about 65 to 70 percent reliable. The technique relies on hurricane correlations with July wind anomalies in regions over North America and the eastern Pacific and North Atlantic oceans to predict hurricane frequency during the main season, which occurs from August through October. Because wind anomalies in those areas have been found to either favor or hinder the development of big hurricanes that strike land in the US, the British team believe they do a better job of predicting worrisome storms than the more complex models.
Keywords: Forecast accuracy; Hurricanes forecasting; Natural disasters; Overlying winds; Sea-level atmospheric pressures; Telltale anomalies